The Precautionary Principle In The Transfer Of Trademark Rights By Notaries - Fenny Riski Diana; Gunardi Gunardi (Publikasi Indonesia, 2023)
The outcome of business activities in the field of services or trade can be identified as a trademark or service mark. The term